The CONCEPTION OF ENERGY CRISIS : A CROSS-SECTIONAL STUDY - Putri Sekar Melati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of this cross-sectional study is to examine how junior high school students and elementary students perceive crisis energy. An online survey, an open-ended inquiry, is used to distribute the instrument. There were 167 research participants, and the percentage included sixth-grade elementary students (14), seventh-grade students (51), eighth-grade students (6), and ninth-grade students (96). The study's findings indicated that ninth-grade students generated the most significant number of concepts, followed by eighth- and seventh-grade students. Students in the ninth grade proposed the idea that "environmental crisis" was the most crucial concept; among eight pupils, "energy limitation" seemed to be the most critical concept; and among high school students, "energy" was the most crucial concept. These findings suggest that more significant ideas about crisis energy can be brought up at higher educational levels. This is because through theoretical or hands-on activities. Ninth graders have gained a greater understanding of energy crisis ideas. The research implications allow educators to teach students more complex concepts connected to crisis energy in addition to the fundamentals.